HIV/AIDS, Climate Change And Disaster Management : Challenges For Institutions In Malawi - Suárez, Pablo (The World Bank, 2008)
Southern African institutions involved in disaster management face two major new threats: the HIV/AIDS pandemic (eroding organizational capacity and increasing vulnerability of the population), and climate change (higher risk of extreme events and disasters). Analyzing the combined effects of these two threats on six disaster-related institutions in Malawi, the authors find evidence of a growing gap between demand for their services and capacity to satisfy that demand. HIV/AIDS leads to staff attrition, high vacancy rates, absenteeism, increased workload and other negative effects enhanced by human resources policies and financial limitations. Many necessary tasks cannot be carried out adequately with constraints such as the 42 percent vacancy rate in the Department of Poverty and Disaster Management Affairs, or the reduction of rainfall stations operated by the Meteorological Service from over 800 in 1988 to just 135 in 2006. The authors highlight implications of declining organizational capacity for climate change adaptation, and formulate recommendations